Prevention Factors For Toddlers Below The Red Line In Surabaya - Fitri Widyanti (Universitas Airlangga, 2022)
Background: Toddlers with BGM (Below the Red Line) are children whose weight for age (BW / U) is below the red line on the KMS, thus indicating malnutrition status. BGM toddlers can be used as an early indicator that the toddler is experiencing nutritional problems that need to be addressed immediately. Objectives: This study analyzes the problems / symptoms and preventive measures for children under the red line in the Wonokusumo Health Center in Surabaya. Methods: This research is an analytic observational study, with a cross sectional design. Subjects were taken by simple random sampling. The population of this research is mothers who have toddlers aged 12-24 months who live in the working area of the Wonokusumo Health Center in Surabaya. The independent variables used are perceived vulnerability, perceived severity, perceived benefits, perceived obstacles, and cues to take action, while the dependent variable used was maternal BGM prevention behavior.Results: This study resulted in several conclusions, namely that there is a relationship between the perceived vulnerability of respondents to taking preventive measures for BGM under five; there is a relationship between the severity felt by the respondents on the prevention measures for BGM under five; there is no relationship between the benefits felt by the respondents on the prevention measures for children under five BGM; there is no relationship between the obstacles felt by respondents to the prevention measures for BGM under five; and there was no relationship between cues to act on precautions for BGM under five.Conclusions: This study views the importance of monitoring the growth of children under five at the posyandu and providing PMT to prevent BGM from under five.